2010
DOI: 10.1371/journal.pone.0011093
|View full text |Cite
|
Sign up to set email alerts
|

Precursor of Advanced Glycation End Products Mediates ER-Stress-Induced Caspase-3 Activation of Human Dermal Fibroblasts through NAD(P)H Oxidase 4

Abstract: BackgroundThe precursor for advanced glycation end products, 3-deoxyglucosone (3DG) is highly upregulated in skin explants of diabetic cutaneous wounds, and has been shown to negatively impact dermal fibroblasts, which are crucial in wound remodeling. 3DG induces apoptosis however; the mechanisms involved in the apoptotic action of 3DG in the pathogenesis of diabetic chronic wounds are poorly understood. Therefore, we sought to delineate novel mechanisms involved with the 3DG-collagen induced apoptosis.Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 58 publications
2
41
0
1
Order By: Relevance
“…This report shows AGEs induce ER stress in human chondrocytes, a finding in agreement with previous reports showing that AGEs mediated ER stress in other cell types [36,37]. Iwawaki et al [38] used a transgenic mouse model to monitor ER stress in vivo , and demonstrated that ER stress occurred in a variety of organs such as liver, spleen, brain, and kidney.…”
Section: Discussionsupporting
confidence: 91%
“…This report shows AGEs induce ER stress in human chondrocytes, a finding in agreement with previous reports showing that AGEs mediated ER stress in other cell types [36,37]. Iwawaki et al [38] used a transgenic mouse model to monitor ER stress in vivo , and demonstrated that ER stress occurred in a variety of organs such as liver, spleen, brain, and kidney.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the recent studies suggesting a growth stimulating role for p38 MAPK, a majority of the studies performed on p38 MAPK have attributed this kinase to cell stress and reduced proliferation. In support of this, we have shown that inhibition of p38 MAPK resulted in caspase-3 activation in dermal fibroblast cultured on native collagen, while it inhibited 3DG-collagen-induced caspase-3 activity [11]. This dichotomy suggests that p38 MAPK can be activated to signal as either a growth kinase or a stress kinase which is dependent upon extracellular stimuli.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, induction of CHOP indicates that ER-initiated apoptosis is induced (23) and our previous study revealed that CHOP plays a role in renal injury (18). Caspase-3 is a downstream target of CHOP and the UPR-independent pathways were demonstrated to culminate in executioner caspase-3 activation and apoptosis in a previous study of proteasome inhibitor-mediated apoptosis (24). Caspase-3 is the final caspase of the apoptotic cascade which activates cytolytic enzymes responsible for apoptosis (25).…”
Section: Discussionmentioning
confidence: 83%